Subcellular Carrier-Based Optical Ion-Selective Nanosensors - Carregal Romero, Susana; Montenegro Martos, Jose María; Parak, Wolfgang; Rivera_Gil, Pilar (Frontiers in Pharmacology, 2012)
In this review, two carrier systems based on nanotechnology for real-time sensing of biologically relevant analytes (ions or other biological molecules) inside cells in a non-invasive way are discussed. One system is based on inorganic nanoparticles with an organic coating, whereas the second system is based on organic microcapsules. The sensor molecules presented within this work use an optical read-out. Due to the different physicochemical properties, both sensors show distinctive geometries that directly affect their internalization patterns. The nanoparticles carry the sensor molecule attached to their surfaces whereas the microcapsules encapsulate the sensor within their cavities. Their different size (nano and micro) enable each sensors to locate in different cellular regions. For example, the nanoparticles are mostly found in endolysosomal compartments but the microcapsules are rather found in phagolysosomal vesicles. Thus, allowing creating a tool of sensors that sense differently. Both sensor systems enable to measure ratiometrically however, only the microcapsules have the unique ability of multiplexing. At the end, an outlook on how more sophisticated sensors can be created by confining the nano-scaled sensors within the microcapsules will be given.